2012
DOI: 10.1111/j.1399-3062.2012.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of transplantation using organs from a donor infected with Klebsiella pneumoniae carbapenemase (KPC)‐producing K. pneumoniae

Abstract: Transmission of pathogens from donor to recipient is a potential complication of organ transplantation. Herein, we describe the clinical course and outcomes of 4 transplant recipients who received tissues from a donor with multi-organ infection with Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae. Recipient 1 underwent simultaneous liver and kidney transplantation for alpha-1 antitrypsin deficiency and alcohol-related cirrhosis, and acute tubular necrosis, respectively. Soon after transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 21 publications
(27 reference statements)
2
66
1
Order By: Relevance
“…87,88 The update also stressed the importance of inter-facility communication, 89 which was shown to be a critical component of successful management of organ transplant recipients from a donor infected with CRKP. 43 Following the 2 recent CRE outbreaks related to contaminated duodenoscopes in the United States and during which one kidney-pancreas transplant recipient died, 90,91 the CDC has also provided guidance on surveillance for bacterial contamination of duodenoscopes after reprocessing. 92 In one outbreak, ethylene oxide sterilization of duodenoscopes halted CRE transmission.…”
Section: Prevention Of Cre Infection In Transplant and Hematologic Onmentioning
confidence: 99%
See 1 more Smart Citation
“…87,88 The update also stressed the importance of inter-facility communication, 89 which was shown to be a critical component of successful management of organ transplant recipients from a donor infected with CRKP. 43 Following the 2 recent CRE outbreaks related to contaminated duodenoscopes in the United States and during which one kidney-pancreas transplant recipient died, 90,91 the CDC has also provided guidance on surveillance for bacterial contamination of duodenoscopes after reprocessing. 92 In one outbreak, ethylene oxide sterilization of duodenoscopes halted CRE transmission.…”
Section: Prevention Of Cre Infection In Transplant and Hematologic Onmentioning
confidence: 99%
“…The recipient's CRKP isolate was phenotypically identical to that of the donor, and he was successfully treated. 43 In the second case, the donor sputum and bronchoalveolar lavage cultures were noted to grow CRKP 2 d following procurement. Recipients of the donor's liver and kidneys did not receive any CRKP-targeted prophylaxis, but the lung transplant recipients received 5 d of parenteral colistin.…”
mentioning
confidence: 99%
“…Concerning the second point, it has been suggested that organs from donors colonized with CPE may be considered for transplantation under well-defined conditions (18,19). However, the risk of cross-infections in these cases appears to be high, and the potential consequences should be carefully considered.…”
mentioning
confidence: 99%
“…These infections are typically caused by pathogens acquired from the hospital environment or already present as colonizers in the transplant recipient (14,17,18). However, cross-transmission of MDR bacteria is also possible from donors infected or colonized by MDR bacteria.…”
mentioning
confidence: 99%
See 1 more Smart Citation